An adaptive transmission technique for low power consumption in wireless sensor networks - Salamah, Muhammed; Abushaaban, Zuhair (My University, 2006)
Sensor networks are potentially very powerful since they can sense the environment in which they are deployed and report sensory data to some processing center, all with little or no human intervention. Currently, such networks support many types of applications such as health, military, environmental, and security. Since the nodes in a wireless sensor network are limited in power source, they must have trade-off mechanisms that give the end user the option of prolonging node lifetime. Radio propagation models have more effect on lifetime than protocols. In this paper, we have proposed an adaptive radio propagation model for sensor networks that minimizes power consumption. The proposed model outperforms the traditionally used models. Copyright 2006 ACM.
IWCMC 2006 - 2006 International Wireless Communications and Mobile Computing Conference --
Keywords: Adaptive transmission; Power consumption; Radio propagation models; Wireless sensor networks